Comportamento tribológico de ferros fundidos vermiculares de alta resistência ensaiados em diferentes níveis de severidade - Wollmann, Daniela (2021)
The tribological performance of the system formed by the cylinder and the components of an internal combustion engine is directly related to the fuel consumption and pollutant emissions. Many countries have been concerned about this issue in the past years due to emission legislative demands. In general, combustion engine blocks are made of grey cast iron and vermicular cast iron. Although, some studies have shown better performance of vermicular iron in this application, allowing reduce wall thicknesses, which could also result in reduced weight and improved performance of the engine. In this scenario, this work had the objective of studying the effect of mechanical resistance and the tribological severity in lubricated contacts of higher strength vermicular cast irons (GJV450 and GJV500 – ISO 16112/2006). In this case, reciprocating lubricated tests in tribometer were performed varying load (75 and 170 N) and temperature (40 and 100 °C). Surfaces of vermicular cast irons consisted on honed engine block cylinders and counterbodies were commercial piston rings of nitrided stainless steel. Furthermore, another testing condition with carbon black added to the lubricant (SAE CF-30) was used to simulate soot produced by incomplete combustion of the engine and to verify the interaction between this particles with the tribological system. Results did not show significant differences in coefficient of friction among testing conditions for both materials. On the other side, scanning electron microscopy and roughness measurements before and after the tribo-tests have shown GJV500 with better performance, presenting less plastic deformation on the surface for the same testing conditions. A tribological merit index was proposed based on the structure height roughness parameters to qualitatively evaluation of wear in each condition and, once more GJV500 presented less topographic modifications after the tests. The analyses of tests performed with carbon black in the lubricant showed that this particles acted as solid lubricant in the contact, reducing the coefficient of friction and preventing the materials from wear.